Development of motor functions in childhood - Rodrigues da Silva, Irisneide; Alves Caribé da Cunha, Alexandre; Ferraz Amaral , Josária (RENEF, 2022)
ABSTRACT Introduction: In addition to being a child’s natural impulse and a form of entertainment, play also works as a tool for the construction of knowledge within the school context. Playful activities should be spontaneous, creative and bring pleasure to those who practice, should reduce tensions and concerns. Justification: This work aims to reflect on the importance of play in learning and motor development, especially in early childhood education. Objective: To analyze the development of motor functions in childhood that occur in the school environment. Methodology: The type of research used will be bibliographic and qualitative, according to the classification proposed by Gil (2012, p.29) the bibliographic research "is elaborated based on previously published material" aiming to create a theoretical basis for the discussion about the importance . Results: Motor development is the process of behavior change, related to age, both in posture and in the child’s movement. Considerations: The contribution of this study is to show the importance of rescuing the playful at school, and having it as a teaching tool for the full performance of students, that teachers and educators working in the field of Physical Education, see the child as a being in development that has play as part of the learning process. Keywords: Physical Education. Motricity. Development.